2008
DOI: 10.1007/s00024-008-0331-y
|View full text |Cite
|
Sign up to set email alerts
|

Earthquakes: Recurrence and Interoccurrence Times

Abstract: The purpose of this paper is to discuss the statistical distributions of recurrence times of earthquakes. Recurrence times are the time intervals between successive earthquakes at a specified location on a specified fault. Although a number of statistical distributions have been proposed for recurrence times, we argue in favor of the Weibull distribution. The Weibull distribution is the only distribution that has a scaleinvariant hazard function. We consider three sets of characteristic earthquakes on the San … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 56 publications
4
34
0
Order By: Relevance
“…It was shown that the time-interval distribution of the system-wide events obeys the Weibull distribution [16,20]. This enables us to the conjecture that the Weibull distribution is induced from the enhancement of the average event size,S.…”
Section: E the Onset Mechanism Of The Weibull Distributionmentioning
confidence: 95%
“…It was shown that the time-interval distribution of the system-wide events obeys the Weibull distribution [16,20]. This enables us to the conjecture that the Weibull distribution is induced from the enhancement of the average event size,S.…”
Section: E the Onset Mechanism Of The Weibull Distributionmentioning
confidence: 95%
“…Each of the three object areas in the three seismic zones have three scenarios, which are categorized by the average recurrence interval with Ms ≥ 6.5, Ms ≥ 7.0, and Ms ≥ 7.5 in every seismic zone. Moreover, References [51,52] defined recurrence interval as the mean value of the time intervals between each historical earthquake event for a given region with a magnitude more than a specified value. However, as the magnitude increases, it becomes more apparent that the seismic data are not complete enough, by which the length of the return period cannot be correctly reflected.…”
Section: Definition Of Scenarios and Recurrence Intervalsmentioning
confidence: 99%
“…Several studies of earthquake catalogues and simulations show that the Weibull distribution is a good match for the empirical return intervals distribution [25][26][27][28][29][30][31][32][33][34]. In addition to statistical analysis, arguments supporting the Weibull distribution are based on Extreme Value Theory [35], numerical simulations of slider-block models [32], and growth-decay mod-els governed by the geometric Langevin equation [6]. The Weibull distribution is also used to model the fracture strength of brittle and quasibrittle engineered materials [36][37][38] and geologic media [39].…”
Section: A Earthquake Return Intervalsmentioning
confidence: 99%